KORELASI MEMAHAMI PANTUN DENGAN KETERAMPILAN MEMPRODUKSI PANTUN SISWA KELAS VII SMP N 34 PADANG - Naneri, Neri Eva; Gani, Erizal; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACT The purpose of this study is to describe three things. First, understanding the traditional poetry seventh grade students of SMP N 34 Padang. Secondly, the writing skills traditional poetry seventh grade students of SMP N 34 Padang. Third, the relationship of understanding the traditional poetry with writing skills traditional poetry seventh grade students of SMP N 34 Padang. This type of research is quantitative, descriptive method and design of the study is correlational. The population was seventh grade students of SMP N 34 Padang, 223 students and the sample are 42 students. Sampling using proportional random sampling technique. Based on the results of research and data analysis, it was concluded that there was a significant relationship between the understanding the traditional poetry with writing skills traditional poetry seventh grade students of SMP N 34 Padang on n-1 degrees of freedom and the significant level of 95%, tcalculate greater than ttable ie 2,60 > 1,68. In other words, if the students' understanding the traditional poetry of good, writing skills traditional poetry students are also good. Conversely, if the students' understanding the traditional poetry of bad, writing skills traditional poetry seventh grade students of SMP N 34 Padang too bad. Kata kunci: korelasi, memahami pantun, keterampilan memproduksi pantun